Quality Control Analysis Using the Six Sigma Approach and Failure Mode and Effect Analysis (Fmea) As an Effort To Reduction Product Defects At CV. Hikmah Jaya Convection - HM, Gatot Basuki; Dari, Yuli Wulan (Journal of Applied Sciences, Management and Engineering Technology, 2024)
CV. Hikmah Jaya Konveksi is a company operating in the convection sector that serves companies, offices, campuses and schools, both private and government. CV. Hikmah Jaya Konveksi as a company operating in the convection sector was founded on January 26 2011. CV. Hikmah Jaya Konveksi is at the address Griya Kebraon Utara VIII No. 27 Surabaya. The aim of this research is to identify types of product defects, find out the sigma level value for defective products produced and analyze the causes of product defects to provide recommendations for existing problems in the company so that it can reduce the level of defects in products. The method used for this research is Six Sigma with the Define, Measure, Analyze, Improve, Control (DMAIC) stages by calculating the company's sigma value and Failure Mode And Effect Analysis (FMEA) for recommendations for improvements to the problem. Based on the results of data processing and data analysis, 3 defects were obtained in the product, including skipped seams, wrinkled seams and slanted seams with an average sigma value of 4.08. Based on the FMEA analysis, the proposed improvements given to minimize defective products are providing training related to sewing SOPs and conducting evaluations. Leaders and Supervisors are responsible for defective products in their respective areas, conducting briefings for each line before production to clarify duties and responsibilities. respectively, providing lubricating oil to machine parts that have the potential to cause friction which causes noise, carried out periodically every 3 weeks, increasing supervision of all workers so that workers can focus when producing uniforms, checking machine maintenance, making maintenance scheduling regularly periodically every month 3 times.